Medical devices regulations, standards and practices - Ramakrishna, Seeram; Tian, Lingling; Wang, Charlene; Liao, Susan; Teo, Wee Eong (Woodhead Publishing, an imprint of Elsevier, 2015)
Medical Devices and Regulations: Standards and Practices will shed light on the importance of regulations and standards among all stakeholders, bioengineering designers, biomaterial scientists and researchers to enable development of future medical devices. Based on the authors' practical experience, this book provides a concise, practical guide on key issues and processes in developing new medical devices to meet international regulatory requirements and standards
Includes bibliographical references and index
Keywords: HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; Medical instruments and apparatus; Surgical instruments and apparatus; Equipment and Supplies / standards